2022
DOI: 10.3390/genes13071230
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Detection of Novel Compound Heterozygous Splice Site Variants of the KIAA0825 Gene in a Fetus with Postaxial Polydactyly Type A

Abstract: Postaxial polydactyly (PAP) is a common abnormality characterized by extra digits on hands and/or feet. To date, sequence variants in seven genes have been identified in non-syndromic PAP. In the present study, a fetus manifesting non-syndromic postaxial polydactyly type A (PAPA) was found by fetal ultrasonography. To better evaluate fetal prognosis, SNP array analysis and trio whole-exome sequencing (trio-WES) were performed to identify the underlying etiology. Although SNP array analysis revealed no abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Previous publications in the literature have reported that nonsense-mediated mRNA decay (NMD) can degrade transcripts containing premature termination codons (PTCs). However, a small fraction of transcripts can escape NMD and remain undegraded, with potential variations in outcomes observed in different mutant forms and/or cell types ( Yao et al, 2022 ; Chu et al, 2023 ; Munoz-Pujol et al, 2023 ; Zheng et al, 2023 ). Similar to c.691 + 1C>A, blood samples in our case of c.791 + 6T>G were collected to identify the consequent changes in mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous publications in the literature have reported that nonsense-mediated mRNA decay (NMD) can degrade transcripts containing premature termination codons (PTCs). However, a small fraction of transcripts can escape NMD and remain undegraded, with potential variations in outcomes observed in different mutant forms and/or cell types ( Yao et al, 2022 ; Chu et al, 2023 ; Munoz-Pujol et al, 2023 ; Zheng et al, 2023 ). Similar to c.691 + 1C>A, blood samples in our case of c.791 + 6T>G were collected to identify the consequent changes in mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the functional consequence of our identified intronic variant, both in vivo (RNA-Seq/RT-PCR) and in vitro (minigene assay) analyses were performed. Patient blood sample is usually accessible for RNA-Seq/RT-PCR analysis of the whole transcriptome or certain genes of interest, which can be routine and quick to complete in diagnostic laboratories ( Fraiman et al, 2021 ; Yao et al, 2022 ; Chu et al, 2023 ; Munoz-Pujol et al, 2023 ; Zheng et al, 2023 ). However, tissue-specific expression can limit this in vivo application, since many genes may not be expressed at a detectable level in blood cells (even though this is not the case for NUS1 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, a total of six other pathogenic variants in KIAA0825 have been reported in subjects with PAP. Four pathogenic variants [p.(Gln198Thrfs*21), p.(Lys725*), p.(Leu17Ser), and p.(Cys48Serfs*28)] were reported in Pakistani families [ 7 , 8 , 31 ] as well as two splice site variants [c.-1-2A>T and c.2247-2A>G] in a Chinese fetus ( Table 3 ) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al 28 reported a fetus manifesting non‐syndromic PAP‐A was found by fetal ultrasonography. They performed SNP array analysis and trio whole‐exome sequencing (trio‐WES) and identified compound heterozygous splice site variants (c.‐1‐2A>T [intron 2] and c.2247‐2A>G [intron 12]) in the KIAA0825 gene, respectively.…”
Section: Classificationmentioning
confidence: 99%
“…They performed SNP array analysis and trio whole‐exome sequencing (trio‐WES) and identified compound heterozygous splice site variants (c.‐1‐2A>T [intron 2] and c.2247‐2A>G [intron 12]) in the KIAA0825 gene, respectively. After performing minigene splice assay and RTPCR assays they showed that the c.‐1‐2A>T variant led to the loss of the initiation codon, and the c.2247‐2A>G variant resulted in skipping of exon 13 28 …”
Section: Classificationmentioning
confidence: 99%